Public Health Aspects of Non-ionizing Radiation in Health determinants in the scope of new public health - Stikova, Elisaveta (Jacobs Verlag, Lage, Germany, 2005)
Exposure to electromagnetic fields is not a new phenomenon. However, dur ing the 20th century, numerous man-made electromagnetic field sources used for individual, industrial and commercial purposes and in medicine have become the focus of the public health interest. All those new and advancing technologies, including power lines, microwave ovens, computer and TV screens, security de vices, radars, mobile cellular phones and their base stations, have made our life richer and easier. At the same time, they have brought with them concerns about possible health risks associated with their use, such as cancer, reduced fertility, memory loss, changes in the behaviour and development of children etc. In response to growing public health concerns over possible health effects from exposure to the electromagnetic field sources, in 1996 the World Health Organization (WHO) launched a large, multidisciplinary International Electro magnetic Field (EMF) Project. This project brings together current knowledge and available resources of key international and national agencies and scientific institutions (1). Despite the feeling of some people that more research needs to be done, the WHO and many other experts concluded that the current evidence does not con firm the existence of any health consequences from exposure to low level electro magnetic fields. There are some gaps in knowledge about the biological effects from long-time exposure and exposure to high levels, so more research is needed in these areas (2). The conflict between concerns about possible health effects from exposure to EMF and the development of electricity supply and telecommunications facilities has led to considerable economic consequences. But the lack of knowledge about the health consequences of technological advances may not be the sole reason for social opposition to innovations and further progress.
Health: Systems – Lifestyles – Policies. A Handbook for Teachers, Researchers and Health Professionals (2nd edition) (eds. Genc Burazeri and Lijana Zaletel Kragelj)
Keywords: public health; non-ionising radiation